Profil saliva pada penyirih di Kecamatan Rembon Kabupaten Tana Toraja Salivary profile of betel quid tobacco chewers in District of Rembon, Tana Toraja - Marcelina Marcelina; Rasmidar Samad (Journal of Dentomaxillofacial Science, 2013)
Betel quid tobacco (BQT) chewing is a process of chewing betel leaves, areca nut, lime, gambier, and tobacco. Chewing and chemical stimulation of BQT can affect the salivary profile. The purpose of this study is to observe the differences of salivary profile such as volume, pH, and salivary inorganic component (Na + and phosphate) between BQT chewers and non-chewers. This study is an observation analytic with cross sectional design on 30-60 years old women that live in Rembon district of Tana Toraja (n=96) using cluster random sampling technique. Salivary volume was measured by measured glass, salivary pH was measured by indicator pH (Macherey-Nagel). The content of the salivary inorganic component was seen using atomic absorption spectrophotometer in BPTP Laboratory, Maros. Data were analyzed by t-test and chi square test using SPSS v 15.0. The result were mean of salivary volume (chewers=3.88 ml/10 s; p=0.051). Mean of salivary pH (chewers=6.92; p=0.001). Mean of salivary Na+ Â (chewers=0.38 ppm; p=0.112), Mg2+ (chewers=11.9 ppm; p=0.002), phosphate (chewers=156.8 ppm; p=0.001), Ca 2+ (chewers=174.8 ppm; p=0.000), K concluded that there was no significant difference on salivary volume, pH, Na+, K+, Ca2+, Mg(chewers=445.9 ppm; p=0.429). It was +and K+ content between chewers and non chewers, but the content of salivary Mg 2+, Ca2+and phosphate had significant difference.